History, Meaning, Context: A Contextualist Theory of Historical Understanding - Szécsi Gábor; Mák Kornél (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-«RIK-U» Kiadó, 2017)
Abstract. The aim of this article is to indicate how a version of intentionalist theory of linguistic communication can be adapted as a part of a contextualist methodology of the history of ideas. In other words, we attempt to clear up the way of harmonizing the theory that communication takes place when a hearer/reader grasps an utterer’s intention with the methodological conception according to which a historian of ideas must concentrate his attention on the context in which in his past author was writing. This article argues that a plausible solution to this problem is suggested in some influential methodological essays by Quentin Skinner. Therefore we shall discuss, on the one hand, the place of an intentionalist model of communication in Skinner’s methodology by providing a brief outline of the main theses of contextualism and intentionalism. On the other hand, we deal with some epistemological problems raised by the application of contextualist method. In particular, we consider the questions that can be raised about the manner in which a historian can grasp an author’s intention.

A tanulmány célja, hogy rávilágítson, miként válhat a nyelvi kommunikáció intencionalista elmélete egy kontextualista eszmetörténeti módszertan részévé. Más szóval, annak tisztázására vállalkozunk, hogy hogyan hozható összhangba az az elmélet, miszerint a kommunikáció akkor valósul meg, ha a hallgató/olvasó megragadja a közlő intencióját, azzal a módszertani koncepcióval, mely szerint egy eszmetörténésznek arra a kontextusra kell összpontosítania a figyelmét, amelyben a múltbeli szerző írása született. Tanulmányunkban amellett érvelünk, hogy a probléma egyik lehetséges megoldását az ismert eszmetörténész, Quentin Skinner munkái sugallják a számunkra. Ezért a kontextualizmus és intencionalizmus fő tételeinek áttekintése mellett egyrészt azt vizsgáljuk, hogy a kommunikáció intencionalista modellje milyen helyet foglal el Skinner módszertanában. Másrészt foglalkozunk néhány, a kontextualista módszer alkalmazásával kapcsolatban felvetődő ismeretelméleti problémával is. Különösképpen azokra a kérdésekre térünk ki, amelyek a múltbeli szövegek születését meghatározó szerzői intenciók megragadásának módját érintik.
https://kmf.uz.ua/wp-content/uploads/2018/02/Limes2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00005710
Keywords: contextualism; intentionalism; Quentin Skinner